DIMENSIONAL ACCURACY OF MACHINE PARTS DURING THE QUENCHING PROCESS - Madaminov Bakhrom Mirodilovich; Yigitaliyev Azimjon Adxamjon ogli (Modern American Journals, 2025)
The quenching process is a critical phase in the heat treatment of machine parts, significantly affecting their dimensional accuracy and overall performance. This study investigates the influence of various quenching parameters—such as cooling rate, quenching medium, material composition, and part geometry—on shape distortions and size variations. By analyzing thermal stresses and phase transformations that occur during rapid cooling, the research highlights the causes of warping, residual stresses, and deformation in machined components. Experimental and simulation-based approaches are employed to assess the extent of dimensional deviations in selected steel alloys. The results underscore the need for optimized quenching strategies to enhance the precision and functional reliability of machine elements. Recommendations are provided for minimizing heat-induced distortions, thereby improving manufacturing quality and component lifecycle.
Keywords: Quenching process, dimensional accuracy, machine parts, heat treatment, thermal stress, warping, deformation, residual stress, cooling rate, steel alloys